Coletivo de cuidados e o setting terapêutico na clínica fonoaudiológica - Cardoso, Flávia (2009)
Speaking of a phonoaudiological clinic implies taking for yourself the litigations that transits in it: to wreck senses and goals and operate , in clinical practice , with theories , procedures and sanitary- associated, personal and collective realities. The feasible existence of a relationship system in the appointments ( between professionals and between professionals with the patient and his/her relatives),is the fact that these mesh affects and produces effects to the care processes of each patient , makes us imagine that the situations created in those contexts need to be evaluated and handled into the therapeutic setting. We call that relatioship mesh, that can constitute in every clinical case, as care collective. It is related to the crossing of these relationships and interlocutions in the patients' therapeutical process. In this sense, we make a reflection of the limits and potentialities of collective work between different health care spheres: school, family, health services, etc. The main goal was to build and systemize technical and conception parameters of handle of these care collectives, as well as reflect about its roles and effects in the phonoaudiological setting, through the study of two clinical cases: first of a four- year-old male with delays in language diagnosis. In this case , the data collective wasn‟t effective. However, the phonoaudiologic search for these constructions had mobilized the child‟s parents creating new perspectives for the continuity of the phonoaudiological work. The second case is of a eight-year-old male with reading and writing disorder. Here, the care collective was structured from the phonoaudiological setting , making intense experience and alternatives for the treatment possible and making different elaborations and patient, his relatives and involved professionals transportation more accessible. This research showed that the so called care collective isn't guaranteed, however, when it happens, the care offer power justifies the work for its construction